Effectiveness of palonosetron in prevention of CHOP induced nausea and vomiting in patients with malignant lymphoma. (2016) - Takamori, Hiroyuki; Nishiura, Nobuko; Masaie, Hiroaki; Yoshida, Hitoshi; Take, Hironori; Ishikawa, Jun; Karasuno, Takahiro
Abstract: AIM: Chemotherapy-induced nausea and vomiting (CINV) remains one of the most common and feared adverse events for patients undergoing chemotherapy. The objective of this prospective study is to evaluate the effectiveness of palonosetron in preventing CINV due to CHOP (cyclophosphamide, doxorubicin, vincristine and prednisolone)-based chemotherapy. Methods: Thirty four chemotherapy-naïve patients with malignant lymphoma received palonosetron 0.75 mg before administration of CHOP-based chemotherapy. We did not use dexamethasone as antiemetic agents. Results: Complete response (CR: no vomiting and no administration of rescue antiemetic agents) rates during acute phase and delayed phase were 100% and 88.2%, respectively. Overall CR rate was 88.2%. Complete control (CC: no emetic episode, no use of rescue medication, and no more than mild nausea) rates during acute phase and delayed phase were 97.1% and 82.4%, respectively. Overall CC rate was 82.4%. Palonosetron was well tolerated and no patient experienced severe adverse events. Conclusion: These results suggest that palonosetron provides protection against acute and delayed CINV associated with CHOP-based chemotherapy for patients with malignant lymphoma.